Pemanfaatan Budaya Lokal dalam Pendidikan di Desa Sapit - Novayani, Irma (Jurnal Manajemen dan Budaya, 2025)
This study analyzes the use of local culture in education in Sapit Village which has great potential in education, but has not been optimal or has not been documented. The purpose of this study is to explore the extent which the local culture of Sapit Village is utilized in education, and what strategies are used by schools and communities in integrating it into the learning process. The method in this study uses a qualitative approach with observation, interview, and documentation methods with respondents consisting of students, traditional leaders and parents. Data analysis uses data reduction, data display and data verification, and to obtain data validity using the data triangulation method. The results of this study indicate that local culture in Sapit Village such as nyongkolan, gendang beleq, begawe, use the Sasak language have great potential to be integrated into formal education, both in terms of learning materials, methods, and values ​​​​that are instilled and contain elements of character education, life skills, and socio-cultural insights that are very important for students. In its utilization, this local culture has begun to be applied on a limited basis, but not yet optimally.